Pengaruh Hormon Asam Indol Asetat yang Dihasilkan Azospirillum sp. terhadap Perkembangan Akar Padi - Puji Lestari; Dwi N. Susilowati; Eny I. Riyanti (Jurnal AgroBiogen, 2007)
Free-living bacteria of thegenus Azospirillum live in close association with rice roots.This bacteria produced indole acetic acid (IAA), a plantgrowth hormon, to the environment. IAA was isolated fromcultures of Azospirillum strains and investigated for its effecton root development and plant height of rice variety IR64 invitro. Rice cultures of variety IR64 were grown in vitro andinoculated with cultures of Azospirilllum. Production of IAAby the bacterium during its growth period in rice culture mediumcontaining different levels of nitrogen was observed.Results of the experiment showed that strains AzospirillumAz15 and Az44 had a high ability to produce IAA, i.e., 57.93μg/ml at 12 days after incubation (DAI) and 40.42 μg/ml at 7DAI, respectively. The IAA production pattern of AzospirillumAz15 and Az44 in the liquid medium were fluctuativeuntil the end of the incubation period, while that of the strainAz7 was linier. Strain Az7 gave a better effect on the rootdevelopment and plant height than strains Az15 and Az44.Treatment combination of strain Az7 and 100% nitrogen gavehighest root development. High level of nitrogen increasedIAA content in the uninoculated culture, while low IAAcontent on the inoculated one. Inoculation the culture withstrain Az7 together with 50% nitrogen application resulted inthe IAA content, root dry weight, root length, fiber root number,and plant height as high as those on cultures containing100% nitrogen (1 mM NH4NO3) without inoculation. Inoculationof rice culture with Azospirillum is expected to reducenitrogen application on rice IR64 by the IAA production asindicated by significant changes in the root growth anddevelopment. A higher concentrations of IAA tend to givebetter effects on the root growth and development of riceIR64.